YUSUF KHAS HADJIB ABOUT SPEECH AND SPEAKERS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article is devoted to the history of the development of oratorical art. Using the example of Yusuf Balasagunsky's creativity, the main properties of the development of this art in the ancient Turkic-speaking environment are shown.